Zapis . poezja, proza, eseje, felietony, no. 11, 1979 - ed. Jerzy Andrzejewski [et al.] (Niezależna Oficyna Wydawnicza N[owa], 1979)
Creation and circulation: Issues no. 19(1981)-21(1982) published only abroad: Index on Censorship (London)